Engineering and fabrication of the “Off the Cuff” pavilion, Fuorisalone 2017, Milan - Beccarelli, Paolo; Maffei, Roberto (2017)
The paper presents the engineering and fabrication of the “Off The Cuff” pavilion designed by Diller Scofidio + Renfro for the exhibition “A Matter of Perception: LINKING MINDS” organised by DAMNº and Mosca Partners at Palazzo Litta for the FuoriSalone2017.